Development of a water-dispersible antimicrobial lipid mixture to inhibit African swine fever virus and other enveloped viruses - Joshua A. Jackman; Roza Izmailyan; Rafayela Grigoryan; Tun Naw Sut; Abel Taye; Hovakim Zakaryan; Charles C. Elrod (Virus Research)
Medium-chain antimicrobial lipids are promising antiviral agents to inhibit membrane-enveloped viruses such as African swine fever virus (ASFV) and influenza A virus (IAV) in livestock applications. However, current uses are limited to feed pathogen mitigation due to low aqueous solubility and the development of water-dispersible lipid formulations is needed for broader application usage. In this study, we report a water-dispersible antimicrobial lipid mixture of monoglycerides and lactylates that can inhibit ASFV and IAV and exhibits antiviral properties in drinking water and feed matrices. The lipid mixture reduced the viral infectivity of membrane-enveloped ASFV and IAV in aqueous solution in a dose-dependent manner but was inactive against non-enveloped encephalomyocarditis virus (EMCV). Additional ASFV experiments supported that the lipid mixture is virucidal, which was corroborated by polymerase chain reaction (PCR) experiments. Feed mitigation experiments demonstrated that the lipid mixture can also inhibit ASFV infectivity and affected the conformational properties of ASFV p72 structural protein in virus-spiked feed. Mechanistic experiments identified that the lipid mixture rapidly disrupted phospholipid membranes in a micelle-dependent manner, which aligns with the virological data while higher concentrations were needed for virucidal activity than for the onset of membrane disruption. These findings support that water-dispersible antimicrobial lipid mixtures can effectively inhibit ASFV and IAV and have practical advantages for drinking water applications compared to existing medium-chain antimicrobial lipid mitigant options that are formulated as dry powders or oils for in-feed applications.